2018
DOI: 10.3389/fphar.2018.00922
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial-Targeting Anticancer Agent Conjugates and Nanocarrier Systems for Cancer Treatment

Abstract: The mitochondrion is an important intracellular organelle for drug targeting due to its key roles and functions in cellular proliferation and death. In the last few decades, several studies have revealed mitochondrial functions, attracting the focus of many researchers to work in this field over nuclear targeting. Mitochondrial targeting was initiated in 1995 with a triphenylphosphonium-thiobutyl conjugate as an antioxidant agent. The major driving force for mitochondrial targeting in cancer cells is the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(80 citation statements)
references
References 119 publications
0
80
0
Order By: Relevance
“…Conjugating DOX with mitochondria penetrating peptide ( Chamberlain et al, 2013 ) generated an adduct called as a mitochondrial-targeted DOX (MtDOX) that can recover cardiomyocytes from mitochondrial damage by activation of compensatory mitochondrial biogenesis without nuclear damage associated with cardiotoxicity ( Jean et al, 2015 ). Although MtDOX is less cytotoxic in drug-sensitive cells, it displays a strong cytotoxic effect in DOX-resistance cells ( Battogtokh et al, 2018 ). Unfortunately, the in vivo anticancer activity of these agents has not been reported yet.…”
Section: Development Of New Dox Formulationsmentioning
confidence: 99%
“…Conjugating DOX with mitochondria penetrating peptide ( Chamberlain et al, 2013 ) generated an adduct called as a mitochondrial-targeted DOX (MtDOX) that can recover cardiomyocytes from mitochondrial damage by activation of compensatory mitochondrial biogenesis without nuclear damage associated with cardiotoxicity ( Jean et al, 2015 ). Although MtDOX is less cytotoxic in drug-sensitive cells, it displays a strong cytotoxic effect in DOX-resistance cells ( Battogtokh et al, 2018 ). Unfortunately, the in vivo anticancer activity of these agents has not been reported yet.…”
Section: Development Of New Dox Formulationsmentioning
confidence: 99%
“…Several studies have reported drug delivery systems for the transport of anticancer compounds to the mitochondria [18], highlighting the use of the lipophilic cations pyridinium [53][54][55] and TPP + [56][57][58][59]. In particular, we showed that TPP + derivatives of gallic acid and GA selectively induce cell death in BC cells [19,20] in a receptor status-independent manner [20] without toxic effects on nontumoral tissues in vivo [21].…”
Section: Discussionmentioning
confidence: 74%
“…An extensively studied strategy for mitochondrial delivery of small molecules is the incorporation of lipophilic cationic groups such as pyridinium or triphenylphosphonium (TPP + ), which allow the accumulation of lipophilic cationic-linked compounds specifically in the "negative" mitochondrial matrix based on the mitochondrial transmembrane potential (∆Ψm) [15][16][17]. Several TPP + -linked small molecules with anticancer effects, such as FDA-approved drugs, polyphenols, therapeutic peptides, and photosensitizers, have been reported [18]. We showed that TPP + -linked natural hydroxybenzoic acids induce OXPHOS inhibition and consistently decrease mitochondrial depolarization and ATP without increasing ROS production.…”
Section: Introductionmentioning
confidence: 99%
“…[53] In mammalian cells,several types of mitochondrial proteins serve as targets for anticancer agents.I np arasites and fungal pathogens the mitochondrion-residing electrontransfer chain and the redox system are important targets for drug development. [53] In mammalian cells,several types of mitochondrial proteins serve as targets for anticancer agents.I np arasites and fungal pathogens the mitochondrion-residing electrontransfer chain and the redox system are important targets for drug development.…”
Section: Targeting the Mitochondrionmentioning
confidence: 99%